1993
DOI: 10.1021/bi00210a030
|View full text |Cite
|
Sign up to set email alerts
|

RNA priming coupled with DNA synthesis on natural template by calf thymus DNA polymerase .alpha.-primase

Abstract: A bovine genomic DNA library was surveyed with respect to the template activity for RNA-primed DNA synthesis by calf thymus DNA polymerase alpha-primase complex. About 7% of the single-stranded DNA clones contained distinct initiation sites consisting of pyrimidine clusters of pyrimidine-rich sequences. The initiation sites were located at or near the 3'-end of the pyrimidine clusters. One of these sequences, containing a 10-mer pyrimidine cluster with major initiation sites, was analyzed in detail. By the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
5
36
0
Order By: Relevance
“…It is possible that during the T-ag-induced melting of double-stranded telomeric DNA in the replication reaction, the G-rich strand forms a G-quartet structure, which does not serve as an efficient template for the DNA replication. In addition, it is known that mammalian DNA polymerase ␣-primase preferentially initiates priming at or near pyrimidine-rich (more than six consecutive pyrimidines) sequences (9,35). This is clearly not the case in mammalian telomeric G-rich strands since they have only two thymines in one repeat.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that during the T-ag-induced melting of double-stranded telomeric DNA in the replication reaction, the G-rich strand forms a G-quartet structure, which does not serve as an efficient template for the DNA replication. In addition, it is known that mammalian DNA polymerase ␣-primase preferentially initiates priming at or near pyrimidine-rich (more than six consecutive pyrimidines) sequences (9,35). This is clearly not the case in mammalian telomeric G-rich strands since they have only two thymines in one repeat.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies demonstrated that the preferred homopolymer substrate for human (21) and mouse (68) pol ot-primase is poly(dT). Several studies have suggested that DNA primase prefers to start at either deoxythymidine-rich sequences (25,74,75) or pyrimidine clusters (59). Collectively, these studies indicated that pyrimidines, particularly thymines, play a critical role in determining where the pol a-primase complex initiates DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Primer initiation sites are rich in thymidine and cytosine residues (13,15,16,26). The high level of thymidine residues should make it more likely that FaraAMP and araAMP might be incorporated into elongating primers by primase within the first 6 bases, resulting in truncated primers that are not elongated by pol ␣.…”
Section: Insertion Of Aracmp Into Full-lengthmentioning
confidence: 99%
“…The sequences of some primer initiation sites have been identified (13)(14)(15)(16), and these sequences support initiation in oligomer templates (15,16). Using an oligonucleotide containing an initiation site for pol ␣-primase, primers with the sequence 5Ј-GGAAGAAAGC-3Ј are generated (16).…”
mentioning
confidence: 99%